ANALYSIS OF PUBLIC SHARE OWNERSHIP, COMPANY CHARACTERISTICS AND DISCLOSURE RATE OF CORPORATE SOCIAL RESPONSIBILTY AT ISLAMIC COMMERCIAL BANKS IN INDONESIA - Cahya, Bayu Tri; Rizqy, Inada; Widi, Widi Savitri Andriasari (Fakultas Ekonomi dan Bisnis Islam, 2022)
CSR disclosure is necessary because it can make the company able to create a conducive atmosphere to be able to carry out sustainable production activities. In addition, CSR disclosure is a business strategy to improve the good image of the company, especially in a region that gets CSR funds from the company. To be able to find out how widespread the level of CSR disclosure can be seen from several factors that can affect it. This research aims to find out the effect of public share ownership, profitability, company size, leverage, and the size of the board of commissioners on CSR disclosure levels. This type of research is quantitative using an explanatory research approach by processing secondary data on the financial statements of Islamic banks in Indonesia obtained from the official OJK website and the website of each bank. The population in this study is all Islamic commercial banks in Indonesia in the period 2016-2019 listed in Islamic banking statistics. While sampling in this study in the form of purposive sampling and obtained data amounting to 36. The data analysis method used in this study is multiple linear regression. The results of this study showed that public share ownership negatively affects CSR disclosure levels and company sizes have a positive and significant effect on CSR disclosure rates, while profitability, leverage, board size have no significant effect on CSR disclosure rates. Keywords: public share ownership, profitability, leverage, board size, corporate social responsilibility